2009
DOI: 10.4070/kcj.2009.39.5.185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Angiotensin Converting Enzyme Inhibitors and Angiotensin Receptor Blockers on Patients Following Ablation of Atrial Fibrillation

Abstract: Background and ObjectivesIt is known that angiotensin converting enzyme inhibitors and angiotensin II type 1 receptor blockers (ACEIs and ARBs, respectively) are effective in preventing atrial fibrillation (AF) in high-risk patients. However, it is not known whether ACEIs and ARBs are effective in preventing the recurrence of AF after catheter ablation.Subjects and MethodsOne hundred fifty-two patients (mean age, 57±10 years; M : F=94 : 58) who underwent catheter ablation due to drug-refractory paroxysmal (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
(23 reference statements)
0
20
0
Order By: Relevance
“…Consequently, 37 articles were excluded, of which 28 did not fulfill the inclusion criteria, five were editorials and comments, two were duplicates, and two did not include the necessary data required for the analysis. Ultimately, nine studies containing 1,607 patients were included in the meta‐analysis . From these nine studies, five were retrospective cohort studies and the remaining four studies were RCTs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, 37 articles were excluded, of which 28 did not fulfill the inclusion criteria, five were editorials and comments, two were duplicates, and two did not include the necessary data required for the analysis. Ultimately, nine studies containing 1,607 patients were included in the meta‐analysis . From these nine studies, five were retrospective cohort studies and the remaining four studies were RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…We identified these subgroups as Zhao and Zhao (1) to represent the different statin dose results. Unfortunately, in one of the RCTs and the five cohort studies, the types and doses of statins used were not specified. Study sizes ranged from 101 to 372 patients, for a total of 1,607 patients.…”
Section: Resultsmentioning
confidence: 99%
“…It is clearly demonstrated that, oxidative stress and inflammation have a significant role in developing left atrial fibrosis and remodeling, which causes left atrial myocardium as susceptible substrate for the occurrence of AF . Likewise, it is widely accepted that oxidative stress and inflammation are also of the important pathophysiologies of atherosclerotic progression …”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that AF and atherosclerosis share common risk factors such as age, hypertension and DM 12)13). Furthermore, several reports demonstrated that oxidative stress and inflammation can play an important role in fibrosis and atrial structural remodeling, which results in the occurrence of AF 23-25). Oakes et al26) reported that the degree of fibrosis of LA myocardial tissue estimated on delayed enhancement magnetic resonance imaging is an independent predictor of recurrence of AF after ablation.…”
Section: Discussionmentioning
confidence: 99%